Chemical Approaches to Therapeutically Target the Metabolism and Signaling of the Endocannabinoid 2-AG and Eicosanoids - Kohnz, Rebecca (2014)
The endocannabinoid system, most popularly known as the target of the psychoactive component of marijuana, Δ(9)-tetrahydrocannabinol (THC), is a signaling network that modulates a diverse range of physiological processes including nociception, behavior, cognitive function, appetite, metabolism, motor control, memory formation, and inflammation. While THC and its derivatives have garnered notoriety in the eyes of the public, the endocannabinoid system is consists of two endogenous signaling lipids 2-arachidonoylglycerol (2-AG) and N-arachidonoylethanolamine (anandamide) that activate cannabinoid receptors CB1 and CB2 in the nervous system and peripheral tissues. This review will focus on recent efforts to chemically manipulate 2-AG signaling, through the development of inhibitors of the 2-AG-synthesizing enzyme diacylglycerol lipase (DAGL) or the 2-AG-degrading enzyme monoacylglycerol lipase (MAGL), and assessing the therapeutic potential of DAGL and MAGL inhibitors in pain, inflammation, degenerative diseases, tissue injury, and cancer.